Influence of Sn and Bi additions on the structures and wear properties of Cu–Sn–P–Ce cBN tools - Han, P.; Li, W.; Peng, J.; Zou, W. (Сверхтвердые материалы, 2018)
In this work Sn and Bi were added to Cu–Sn–P–Ce for improving its microstructures and properties. Structures of the three matrices were investigated by XRD, SEM and EDS. The Cu₄₁Sn₁₁ became the main microstructure with some pores, the grinding ratio increased, and the grinding efficiency improved slightly with the addition of Sn to Cu–Sn–P–Ce. Bi was distributed in the form of simple substance, the grinding ratio increased, and the grinding efficiency greatly reduced with the addition of Bi to Cu–Sn–P–Ce. Методами XRD, SEM та EDS досліджено структуру матриць Cu–Sn–P–Ce з добавками Sn і Bi, які додавали для поліпшення мікроструктури і властивостей матеріалу. При додаванні Sn у Cu–Sn–P–Ce основою мікроструктури став Cu₄₁Sn₁₁ з невеликою кількістю пор, коефіцієнт шліфування збільшився, а ефективність шліфування дещо покращилася. При додаванні Bi у Cu–Sn–P–Ce він був розподілений у вигляді простої субстанції, коефіцієнт шліфування збільшився, а ефективність шліфування значно зменшилася. Методами XRD, SEM и EDS исследована структура матриц Cu–Sn–P–Ce с добавками Sn и Bi, которые вводили для улучшения микроструктуры и свойств материала. При добавлении Sn в Cu–Sn–P–Ce основой микроструктуры стал Cu₄₁Sn₁₁ с небольшим количеством пор, коэффициент шлифования увеличился, а эффективность шлифования немного улучшилась. При добавлении Bi в Cu–Sn–P–Ce он распределялся в виде простой субстанции, коэффициент шлифования увеличился, а эффективность шли фования значительно уменьшилась.